Metallomics and the Cell - Banci, Lucia; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Metallomics and the Cell provides in an authoritative and timely manner in 16 stimulating chapters, written by 37 internationally recognized experts from 9 nations, and supported by more than 3000 references, several tables, and 110 illustrations, mostly in color, a most up-to-date view of the "metallomes" which, as defined in the "omics" world, describe the entire set of biomolecules that interact with or are affected by each metal ion. The most relevant tools for visualizing metal ions in the cell and the most suitable bioinformatic tools for browsing genomes to identify metal-binding proteins are also presented. Thus, this book is of relevance for structural and systems biology, inorganic biological chemistry, genetics, medicine, diagnostics, as well as teaching, etc. Lucia Banci is a bioinorganic chemist and a structural biologist who is studying, among various topics, metal transport and metal homeostasis processes. She is aiming towards a cellular perspective in the spirit of mechanistic systems biology, with the goal of describing functional processes with atomic resolution in a cellular context.
Keywords: Life sciences; Human physiology; Chemistry, inorganic; Pharmacy; Science -- Study and teaching; Life Sciences; Life Sciences, general; Inorganic Chemistry; Human Physiology; Science Education; Pharmacy